Oscar Wilde’s Moral Philosophy: A Synthesis between Aestheticism and The Picture of Dorian Gray - Akudolu, Linus Oluchukwu; Okwuosa, Ikechukwu K.; Okeke, Ifeanyi J.; Okolie, Charles N.; Ofoegbu, Francis C.; Ojiegb, Valentine N.; Akpa, Christopher O.; Solomon, Kingsley C.; Eze, Hillary O.; Okolo, Chinwe Jane (Harmonia: Journal of Arts Research and Education, 2024)
The exaggeration of Oscar Wilde’s aestheticism that the work of art is purely for beauty and pleasure and has nothing to do with morality makes it very difficult for his moral philosophy to be conceived. Even his novel, The Picture of Dorian Gray, which is meant to balance his exaggeration of pleasure in his aestheticism, is often misinterpreted as an aesthetic eulogy. At the same time, some see it as a pure contradiction to his former philosophic position. This paper, therefore, attempts to identify his moral philosophy through a dialectic study of his aestheticism and The Picture of Dorian Gray. As it is qualitative research, the authors source their data primarily from literary works by Oscar Wilde, while other library materials serve as secondary sources. Various philosophical tools, especially dialectics and hermeneutics, are applied in data interpretation. The finding is that contrary to the expectation and assumption of many scholars, ethical hedonism rather than aesthetic hedonism is his moral philosophy.